Mononuclear muscle cells in Drosophila ovaries revealed by GFP protein traps - Hudson, Andrew M. (2007)
Genetic analysis of muscle specification, formation and function in model systems has provided valuable insight into human muscle physiology and disease. Studies in Drosophila have been particularly useful for discovering key genes involved in muscle specification, myoblast fusion, and sarcomere organization. The muscles of the Drosophila female reproductive system have received little attention despite extensive work on oogenesis. We have used newly available GFP protein trap lines to characterize of ovarian muscle morphology and sarcomere organization. The muscle cells surrounding the oviducts are multinuclear with highly organized sarcomeres typical of somatic muscles. In contrast, the two muscle layers of the ovary, which are derived from gonadal mesoderm, have a mesh-like morphology similar to gut visceral muscle. Protein traps in the Fasciclin 3 gene produced Fas3::GFP that localized in dots around the periphery of epithelial sheath cells, the muscle surrounding ovarioles. Surprisingly, the epithelial sheath cells each contain a single nucleus, indicating these cells do not undergo myoblast fusion during development. Consistent with this observation, we were able to use the Flp/FRT system to efficiently generate genetic mosaics in the epithelial sheath, suggesting these cells provide a new opportunity for clonal analysis of adult striated muscle.